Morphological disparity and evolutionary transformations in the primate hyoid apparatus. Issue 162 (January 2022) - Li, Peishu; Ross, Callum F.; Luo, Zhe-Xi
Abstract: The hyoid apparatus plays an integral role in swallowing, respiration, and vocalization in mammals. Most placental mammals have a rod-shaped basihyal connected to the basicranium via both soft tissues and a mobile bony chain—the anterior cornu—whereas anthropoid primates have broad, shield-like or even cup-shaped basihyals suspended from the basicranium by soft tissues only. How the unique anthropoid hyoid morphology evolved is unknown, and hyoid morphology of nonanthropoid primates is poorly documented. Here we use phylogenetic comparative methods and linear morphometrics to address knowledge gaps in hyoid evolution among primates and their euarchontan outgroups. We find that dermopterans have variable reduction of cornu elements. Cynocephalus volans are sexually dimorphic in hyoid morphology. Tupaia and all lemuroids except Daubentonia have a fully ossified anterior cornu connecting a rod-shaped basihyal to the basicranium; this is the ancestral mammalian pattern that is also characteristic of the last common ancestor of Primates. Haplorhines exhibit a reduced anterior cornu, and anthropoids underwent further increase in basihyal aspect ratio values and in relative basihyal volume. Convergent with haplorhines, lorisoid strepsirrhines independently evolved a broad basihyal and reduced anterior cornua. While a reduced anterior cornu is hypothesized to facilitate vocal tract lengthening and lower formant frequencies in some mammals, our results suggest vocalization adaptations alone are unlikely to drive the iterative reduction of anterior cornua within Primates. Our new data on euarchontan hyoid evolution provide an anatomical basis for further exploring the form-function relationships of the hyoid across different behaviors, including vocalization, chewing, and swallowing.